Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1093/humrep/10.6.1341
|View full text |Cite
|
Sign up to set email alerts
|

Physiology: In-vivo studies on ovarian insulin-like growth factor I concentrations in human preovulatory follicles and human ovarian circulation

Abstract: In some recent hypotheses, the ovary has been indicated as a source of insulin-like growth factor (IGF)-I, with synthesis regulated from local steroidal and non-steroidal substances. We measured IGF-I concentrations in both serum and follicular fluid of women undergoing in-vitro fertilization (IVF) and embryo transfer, in both induced and spontaneous cycles. It was found that serum and follicular IGF-I concentrations were correlated with follicular morphology, oocyte maturity, steroid concentrations and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 0 publications
0
23
1
Order By: Relevance
“…The association of a fall in IGF-I levels with a higher number of immature oocytes in PCOS patients suggests that the bioavailability of IGF-I is integral to the mature oocyte in these patients. Several authors have found that in normally ovulating patients, follicular fluid IGF-I concentrations correlated with the degree of oocyte maturity (8,9,29) We did detect significantly different levels of IGFBP-3 and discrepant trends of serum IGFBP-3 levels during stimulation in PCOS and control patients. Serum IGFBP-3 levels decrease during FSH stimulation in normally ovulating patients (16,17,30).…”
Section: Discussioncontrasting
confidence: 40%
“…The association of a fall in IGF-I levels with a higher number of immature oocytes in PCOS patients suggests that the bioavailability of IGF-I is integral to the mature oocyte in these patients. Several authors have found that in normally ovulating patients, follicular fluid IGF-I concentrations correlated with the degree of oocyte maturity (8,9,29) We did detect significantly different levels of IGFBP-3 and discrepant trends of serum IGFBP-3 levels during stimulation in PCOS and control patients. Serum IGFBP-3 levels decrease during FSH stimulation in normally ovulating patients (16,17,30).…”
Section: Discussioncontrasting
confidence: 40%
“…Moreover, in vitro studies have shown that IGF-II increases the release of E 2 from cultured human GCs in a dose-dependent manner (28). In contrast, FF levels of IGF-I at the preovulatory stage are considerably lower than serum levels, indicating that IGF-I in FF is probably derived from peripheral circulation diffusion (17,29). Although IGF-I mRNA is not detected in GCs of the mature human ovary, IGF-I receptor mRNA is abundant in GCs of both Graafian and atretic follicles (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…1,15 Moreover, serum levels of IGF-I are higher than follicular fluid levels in the preovulatory stage in women undergoing IVF. 18,19 This implies that IGF-I in follicular fluid is probably derived from the peripheral circulation. 20 Serum levels of IGF-I in women, therefore, may determine follicular levels of IGF-I, which subsequently affect oocyte maturation.…”
Section: Commentmentioning
confidence: 99%